THE EFFECT OF GOOD CORPORATE GOVERNANCE, LEVERAGE AND PROFITABILITY ON PROFIT MANAGEMENT IN REGISTERED MANUFACTURING COMPANIES IN INDONESIA STOCK EXCHANGE - Sinaga, Doharman (Asosiasi Dosen Akuntansi Indonesia, 2019)
The objective of the research was to analyse the influence of Good Corporate Governance, Leverage, and Profitability on Earning Management in the Manufacture Companies listed in the Indonesia Stock Exchange. The research used explanatory research method. The population was 144 manufacture companies with total observation of 318, and 106 of them were used as the samples, taken by using proportional random sampling technique. The data were gathered by conducting documentary study and analysed by using panel data regression analysis. The result of the research showed that, simultaneously, Good Corporate Governance, Leverage, and Profitability had the influence on Earning Management. Partially, Good Corporate Governance and Leverage did not have any influence on Earning Management, while Profitability had the influence on Earning Management.